2006
DOI: 10.1292/jvms.68.567
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MAP Kinases and Connexins in the Differentiation of Rat Mammary Epithelial Cells

Abstract: ABSTRACT. Gap junctional intercellular communication (GJIC) is involved in the regulation of many cellular processes. MAP kinases are known to affect GJIC and phosphorylation of connexin (Cx). MAP kinases can also be a regulator of cell proliferation and growth. This study was undertaken to show the relevance between expression patterns of Cxs and MAP kinases in rat mammary epithelial cells (RMECs). In order to characterize the RMECs, they were stained with Peanut lectin, which indicates most alveolar epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…[68] It has been observed that highly proliferating malignant cells have less gap junctions than the most differentiated ones. [69] In particular, connexin 43 (Cx43) is a tumor suppressor,[69] and its expression is reduced in various tumors.…”
Section: Phenylbutyrate and Cancermentioning
confidence: 99%
“…[68] It has been observed that highly proliferating malignant cells have less gap junctions than the most differentiated ones. [69] In particular, connexin 43 (Cx43) is a tumor suppressor,[69] and its expression is reduced in various tumors.…”
Section: Phenylbutyrate and Cancermentioning
confidence: 99%
“…The mammary gland epithelial components are thought to arise from stem cells that undergo both self-renewal and differentiation. Self-renewal has been shown to be regulated by the MAPK, Wnt/beta-catenin, Notch, Hedgehog, transforming growth factor (TGF)-beta, PTEN and Bmi-1 signaling pathways [1,9,21,24,30]. Wiseman and Werb suggested factors intrinsic to these stem cells as well as their interactions with stromal cells and the extracellular matrix are important for normal morphogenesis of the gland [32].…”
Section: Distinguishing Features Of Mammary Epithelial Stem Cellsmentioning
confidence: 99%
“…The resulting intercellular communication is essential for both proliferation and activation of differentiation pathways (Seo et al, 2006). It has been shown that highly proliferating malignant cells have less gap junctions than more differentiated ones (Yamasaki and Naus, 1996).…”
mentioning
confidence: 99%